Theoretical Studies Green Hospital - Harison Sigalingging, Brando; ., Nadiroh; ., Sucahyanto (KnE Social Sciences, 2020)
The increasing number of hospitals has an influence on the damage to the environment if it is not well managed. Environmental damage is a joint responsibility of the government, private sector and the community. In Indonesia at this time there is not even a hospital that is included in the category of environmentally friendly hospitals or green hospitals, but the government prepares in 2020 each hospital is expected to participate in managing the hospital environment properly by always considering aspects of health, economy, ecology and social so that the principle of fulfilling the concept of sustainable development in the health sector will be fulfilled to the maximum, and hospitals can play an active role in minimizing the impact of climate change. This research uses descriptive analysis techniques. From the results of this study stated that of the 10 green hopsital categories of the world hospital HUSADA still needs to be prepared. Keywords: Theoretical Studies, Green Hospital, Hospital Environment